Vocational guidance and development of competences - Alí Jafella, Sara Jimy; Villafañe de Gil, Dora (2003)
The present "post modern" socio-cultural modalities and the restrictions of the economic globalization lead us to reflect about the configuration of the transformations in the Vocational Guidance, committed to the concepts of "freedom", "epistemological knowledge", "competences of the subject and new roles of the school. This first exploratory incursion if the research has the purpose of retrieving the concept of freedom from the existential philosophers Heidegger and Sartre and of introducing the subject of "competences" from the social theory of Habermas. The aim is to establish new bonds between the Vocational Guidance and the above-mentioned philosophical lineaments: the freedom of the subjects and the possibility of development of those "competences" that allow to establish social, ethical and epistemological interrelations in the sphere of the Vocational Guidance, that promote a greater solidarity facing the "era of emptiness" of the post-modernity supported by Lipovestky.
Keywords: Freedom to choose; Competences; Vocational guidance; Postmodernity; Sociología ocupacional; Orientación vocacional; Libertad; Vocación; Trabajo de investigación